Review of Chirped Fiber Bragg Grating (CFBG) Fiber-Optic Sensors and Their Applications - Tosi, Daniele (MDPI, 2018)
Fiber Bragg Gratings (FBGs) are one of the most popular technology within fiber-optic sensors, and they allow the measurement of mechanical, thermal, and physical parameters. In recent years, a strong emphasis has been placed on the fabrication and application of chirped FBGs (CFBGs), which are characterized by a non-uniform modulation of the refractive index within the core of an optical fiber. A CFBG behaves as a cascade of FBGs, each one reflecting a narrow spectrum that depends on temperature and/or strain. The key characteristic of CFBGs is that their reflection spectrum depends on the strain/temperature observed in each section of the grating; thus, they enable a short-length distributed sensing, whereas it is possible to detect spatially resolved variations of temperature or strain with resolution on the order of a millimeter over the grating length. Based on this premise, CFBGs have found important applications in healthcare, mechanical engineering, and shock waves analysis, among others. This work reviews the present and emerging trends in CFBG sensors, focusing on all aspects of the sensing element and outlining the application case scenarios for which CFBG sensors have been demonstrated.
Keywords: fiber optic sensors; Fiber Bragg Grating (FBG); Chirped Fiber Bragg Grating (CFBG); FBG sensors; photosensitivity